Produção de beterraba em função de doses de torta de mamona em cobertura - Silva, Priscilla N. L. [UNESP]; Lanna, Natália B. L. [UNESP]; Cardoso, Antonio I. I. [UNESP] (My University, 2016)
The objective of this study was to evaluate the influence of castor bean cake rates applied in topdressing in beet production. Two experiments were carried out in São Manuel, São Paulo State, Brazil, from September 5 to December 10, 2012. Rates of castor bean cake were evaluated (0, 150, 300, 450 and 600 g/m2), as well as a control with inorganic fertilization in topdressing (129 g/m2 ammonium sulfate and 24 g/m2 potassium chloride), totalizing six treatments in randomized blocks design, with four replications. In the first experiment, base fertilization consisted of organic compost (40 t/ha) and in the second experiment, besides the organic compost, inorganic fertilization was applied using NPK 4-14-8 (1.7 t/ha). The top dressing fertilization in the experiments was divided into three applications, at intervals of 14 days after transplantation. Castor bean cake rates influenced none of all evaluated characteristics in treatments receiving organic planting fertilization associated with inorganic fertilization, and the average yield obtained was 37.5 t/ha. In the absence of inorganic planting fertilization, with the application of up to 600 g/m2 castor bean cake in topdressing, a linear increase in all characteristics was obtained. For each 100 g/m2 castor bean cake applied, we obtained an increase of 7.2 g of root fresh weight, 1.5 mm in the root diameter and 2.2 t/ha in the yield, with maximum values of root fresh weight (139.5 g), root diameter (6.5 cm) and yield (42.9 t/ha) obtained in the highest rate (600 g/m2).
Beet production depending on rates of castor bean cake as topdressing
Keywords: Beta vulgaris; Dry mass; Organic fertilizer